Are Refugees Different from Economic Immigrants? : Some Empirical Evidence on the Heterogeneity of Immigrant Groups in the United States - Kalena E. Cortes (Institute for the Study of Labor (IZA), 2004)
This paper analyzes how the implicit difference in time horizons between refugees and economic immigrants affects subsequent human capital investments and wage assimilation. The analysis uses the 1980/1990 Integrated Public Use Samples of the Census to study labor market outcomes of immigrants who arrived in the U.S. from 1975 to 1980. I find that in 1980 refugee immigrants in this cohort earned 6 percent less and worked 14 percent fewer hours than economic immigrants. Both had about the same level of English skills. The two immigrant groups had made substantial gains by 1990; however, refugees had made greater gains. In fact, the labor market outcomes of refugee immigrants surpassed those of economic immigrants. In 1990, refugees from the 1975-1980 arrival cohort earned 20 percent more, worked 4 percent more hours, and improved their English skills by 11 percent relative to economic immigrants. The higher rates of human capital accumulation for refugee immigrants contribute to these findings.
Keywords: J24; J31; F22; C81; 330; refugee and economic immigrants; human capital investment; wage growth; Flüchtlinge; Einwanderung; Internationale Arbeitsmobilität; Vergleich; Bildungsinvestition; Lohn; Soziale Integration; Schätzung; Vereinigte Staaten